ZIONISME DAN BERDIRINYA NEGARA ISRAEL - Saude Saude (Hunafa: Jurnal Studia Islamika, 2006)
Zionism is a political movement established on Judism doctrines. The very prominent mission of this movement is to establish an independent   state of Israel. The Jews  claim themselves to be the choosen people. In addition, they claim that Israel is the holy land promised by God. Therefore, they keep on  fighting the Palestinians for the promised holy land.      Kata Kunci: Zionisme, Yahudi, Israel